Leading Hand Hygiene from the Circle of Concern to the Circle of Influence - Khuan, Ng Wai (International Journal of Infection Control, 2012)
Background: The rate of healthcare-associated infection (HAI) in Mafraq hospital was 1.6 per 1000 patient days and it was higher than the 2010 benchmark from Centers for Disease Control & Prevention (CDC), which is 0.4 per 1000 patient days. The following paper is going to present a successful cultural and behavioral transformation at Mafraq Hospital which resulted in improvement of hand hygiene practices. Methods: The infection preventionists and marketing team had worked together with the executive team to brainstorm and develop interventions which reduce barriers to improve hand hygiene compliance. The massive hand hygiene campaigns phase 1 and 2 were held in July and October 2010.Results: After 15 months, the hand hygiene compliance rate increased to 86% in July 2011. As hand hygiene compliance improved, it was noted that, during the same time, the healthcare-associated infection rates decreased to 0.4 per 1000 patient days in July 2011.Conclusion: The evidence from the hand hygiene campaigns launched in Mafraq Hospital showed a decrease in healthcare-associated infections as the compliance increased. Mafraq hospital has a significant increase of hand hygiene compliance by 64% in 15 months period and therefore, it can be concluded that hand hygiene compliance can be significantly improved through 'Hand Hygiene' campaigns. Key Words: Healthcare-associated infection (HAI); hand hygiene; compliance; campaign; Glitter Bug Maxicam; hand shape mascot.